Consciousness and Action Control - Ezequiel Morsella (Frontiers Research Topics, 2014)
The basic nuts and bolts underlying human behavior remain mysterious from a scientific point of view. Everyday acts - naming an object, suppressing the urge to say something, or grabbing a waiter's attention with a "cappuccino, please" - remain difficult to understand from a mechanistic standpoint. Despite these challenges, research has begun to illuminate, not only the basic processes underlying human action production, but the role of conscious processing in the control of behavior. This Research Topic, "Consciousness and the Control of Action," is devoted to surveying and synthesizing these developments from disparate fields of study.